Between Infection and Malignancy: Key Clues to Distinguish Osteosarcoma from Osteomyelitis - Marcjasz, Piotr; Bioły, Anna; Dryja, Patryk; Boczar, Agata; Buliszak, Agnieszka; Babczyńska, Monika (Quality in Sport, 2025)
Introduction and aim: Osteosarcoma (OS) is a primary malignant bone tumor of youth, while osteomyelitis (OM) is an inflammatory bone infection. Despite of different etiologies, OS and OM can present with overlapping clinical and radiologic features. This paper aims to review the pathophysiology of OS and OM, indicating their clinical similarities, discuss difficulties in diagnosing and differentiating them. Material and methods of research: A thorough literature review was performed using PubMed, Web of Science and Embase. State of Knowledge: Osteosarcoma derives from mesenchymal osteoblast precursors and is characterized by malignant osteoid production [1]. It predominantly affects adolescents, often near the metaphyses of long bones, with rapid bone turnover [1]. Osteomyelitis is a bone infection that triggers an inflammatory cascade causing bone destruction, necrosis, and reactive new bone formation [3]. Clinically, both OS and OM cause localized bone pain, swelling and systemic signs, which can lead to one being mistaken for the other [7]. Radiologically, both may show bone lysis, periosteal reaction, and soft-tissue changes, compounding the diagnostic dilemma [6]. Because symptoms and imaging findings can overlap, misdiagnoses occur. Conclusions: OS and OM have distinct pathophysiologies – one neoplastic, one infectious – yet they can mirror each other clinically and radiographically. Proper diagnosis is critical as treatments diverge.